Optimalisasi Biaya Produksi Menggunakan Metode Liniear Programming Dalam Rangka Pengupasan Overburden di KUD Sinamar Sakato, Sinamar, Kabupaten Dharmasraya, Provinsi Sumatera Barat - M Sahrudin; Rudy Anarta; Adree Octova; Admizal Nazki (Journals Mining Engineering : Bina Tambang, 2022)
The problem faced by KUD Sinamar Sakato at this time is the occurrence of Sliding Back Filling material in July 2021 from PIT 1 IUP PT SLN which borders KUD Sinamar Sakato. Then in July 2022, Fleet Loading Point Overbuden Removal was added which was originally 4 Fleet to 5 Fleet, of which 3 Fleet only focuses on the sliding material back filling area which is still happening today. Which is where the remaining 2 Fleet focuses on the Front Loading Coal area, and also not achieving the overburden production target in the Pit Pyramid in June-July 2022 of 150,000 BCM while the actual is 141,500 BCM/month. This research was conducted to calculate and analyze the optimal number of digging and loading equipment according to the production target and to get the minimum loading and hauling costs. The optimization method used is the match factor method and the linear programming method using POM Software for Windows, Lingo. and manual calculations using the simplex method. Based on calculations using POM for Windows software, lingo and Linear Programming Simplex Method, it is obtained that the number of dump trucks planned is 12 units, which previously was 15 units. then the optimal production obtained for stripping overburden material is 156.459 BCM/month from 150,000 BCM/hour with a production cost of 0.85 USD/BCM from 1.11 USD/BCM.